Effect of salicylic acid and mycorrhizal symbiosis on improvement of fluoranthene phytoremediation using tall fescue (Festuca arundinacea Schreb). (October 2019) - Rostami, Majid; Rostami, Saeid
Abstract: Polycyclic aromatic hydrocarbons are an important group of pollutants that are widely distributed in the environment. The present study aimed to investigate the effect of salicylic acid (a phenolic phytohormone) and mycorrhizal fungi on the growth and phytoremediation ability of tall fescue in the soil contaminated by fluoranthene. The initial concentrations of fluoranthene in this study were 100, 200, and 300 mg kg -1 . The experimental treatments were included: T0 uncultivated soil; T1 cultivated soil with tall fescue; T2 cultivated soil with tall fescue + salicylic acid application; T3 cultivated soil with tall fescue + application of mycorrhizal fungi; T4 cultivated soil with tall fescue + salicylic acid and mycorrhizal fungi application; and P planting tall fescue in uncontaminated soil. The removal of fluoranthene was measured after 90 days. Furthermore, at the end of the experiment, the amount of shoot and root biomass, soil bacteria, and dehydrogenase activity were measured. According to the results, in all levels of contamination, removal of fluoranthene in cultivated treatments significantly was higher than uncultivated treatments. Increasing the concentration of fluoranthene had a negative effect on the shoot and root biomass in different treatments. Salicylic acid and mycorrhizal fungi significantly increased the shoot and root biomass and also the number of soil bacteria, dehydrogenase activity, and fluoranthene removal in T2, T3, and T4 treatments compared to T1. At the highest concentration of fluoranthene, as a result of simultaneous application of salicylic acid and mycorrhizal fungi (T4), the fluoranthene removal increased by 63, 21, 13, and 16% in comparison with T0, T1, T2, and T3, respectively. Based on the results, salicylic acid and mycorrhizal fungi, either alone or in combination, have a significant effect on the improvement of phytoremediation potential in tall fescue. Highlights: Using mycorrhiza for phytoremediation of fluoranthene is recommendable. As a result of plant root growth, fluoranthene decomposition in the soil increased. In the presence of festuca, the efficiency of the fluoranthene removal increased.